The effect of drivers gender on the perception of Portuguese road safety communication campaigns - Rodrigues, Helena Sofia (2017)
The road safety campaigns use a range of media and marketing communication techniques to alert drivers to take appropriate behavior on the road. The aim of this study was to investigate how gender differences influence the behavior and attitude of the Portuguese drivers regarding driving as well as the attitude toward the road safety campaigns. In Portugal, there are no studies that analyze the gender difference related to road safety, which reinforces its relevance. To implement this purpose, firstly it was described the profile of drivers by gender regarding a set of behavioral variables. The attitude of drivers toward the road safety communication campaigns was analyzed and drivers were grouped by clusters, aiming its characterization as possible targets of communication actions for road safety marketing.